ENERGY EFFICIENCY IN THE OLIVE GROVES AND OLIVE OIL MILLS - Baptista, F (2023)
The assessment of energy consumption in agriculture has been focused mainly on direct energy. However, a very important part of the total energy consumed on farms is related to indirect energy, e.g. the energy used in the production of other inputs, such as fertilizers and others. Various studies carried out with data from olive groves with different planting intensities made possible to assess direct and indirect energy consumption, identifying the production factors with the greatest impact. In the olive mills, studies of energy consumption in the several processing phases, combined with knowledge of the energy balance, make it possible to identify critical points and the appropriate technologies to improve energy efficiency. In the Alentejo Olive Oil Sustainability Plan (AOSP) there are chapters dedicated to Energy Efficiency in the Olive Groves and in the Olive Mills, where the criteria and categories considered for the definition of energy sustainability throughout the production chain are defined. In both, the objective is to assess the level of sustainability of the producers (pre-initial, initial, intermediate or developed).